Promoting the Self-Regulation of Stress in Health Care Providers: An Internet-Based Intervention - Gollwitzer, Peter M.; Mayer, Doris; Frick, Christine; Oettingen, Gabriele (Frontiers in Psychology, 2018)
The aim of our internet-based intervention study was to find out whether healthcare professionals can autonomously down-regulate the stress they experience at their workplace, using an established self-regulation tool called Mental Contrasting with Implementation Intentions (MCII). Applying MCII to reduce stress implied for our participants to repeatedly engage in a mental exercise that 1) required specifying a wish related to reducing stress, 2) identifying and imagining its most desired positive outcome, 3) detecting and imagining the obstacle that holds them back, and 4) coming up with an if-then plan on how to overcome it. We recruited on-line nurses employed at various health institutions all over Germany, and randomly assigned participants to one of three groups. In the MCII group (n = 33), participants were taught how to use this exercise via email and the participants were asked to engage in the exercise on a daily basis for a period of three weeks. As compared to two control groups, one being a no-treatment control group (n = 35) and the other a modified MCII group (n = 32), our experimental MCII group showed a reduced stress level and an enhanced work engagement. We discuss the strengths and weaknesses of the present study as well as ways to intensify MCII effects on stress reduction.